2023
DOI: 10.1136/archdischild-2022-324977
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset sepsis in very preterm infants in Norway in 2009–2018: a population-based study

Abstract: ObjectiveTo evaluate epidemiology and outcomes among very preterm infants (<32 weeks’ gestation) with culture-positive and culture-negative late-onset sepsis (LOS).DesignCohort study using a nationwide, population-based registry.Setting21 neonatal units in Norway.ParticipantsAll very preterm infants born 1 January 2009–31 December 2018 and admitted to a neonatal unit.Main outcome measuresIncidences, pathogen distribution, LOS-attributable mortality and associated morbidity at discharge.ResultsAmong 5296 ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…CoNS, where most isolates came from infants born extremely- or very preterm, was the most frequent causing pathogen in LOS. This is consistent with previous studies [ 10 , 26 , 27 ]. The CFR for CoNS seen in our study was in line with previous studies [ 10 , 33 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…CoNS, where most isolates came from infants born extremely- or very preterm, was the most frequent causing pathogen in LOS. This is consistent with previous studies [ 10 , 26 , 27 ]. The CFR for CoNS seen in our study was in line with previous studies [ 10 , 33 ].…”
Section: Discussionsupporting
confidence: 94%
“…The incidence of GPB sepsis in this study was 1.47/1000 LB, which is more than 4 times the incidence for GNB sepsis (0.35/1000 LB) in our area, but with a lower SFR (2.8% versus 16.8%) and CFR (9.5% versus 28.0%) [ 14 ]. This result is in line with previous studies showing a higher mortality rate for GNB sepsis compared to GPB sepsis [ 10 , 26 , 27 ]. Few studies have reported on GPB-sepsis separately, but our GPB-SFR in LOS is like that of a recent Norwegian study [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study highlights a concerning rise of Gram-negative IBIs in infants from April 2011 to March 2019 in England, driven primarily by an increase in incidence of late-onset infection in both neonates and infants. Similar increases in late-onset infections have been observed in the USA, The Netherlands and Norway; however, these were largely driven by Gram-positive IBIs or were seen primarily in premature infants 21–23. Prematurity remains one of the main risk factors for early-onset and late-onset IBIs 24 25.…”
Section: Discussionmentioning
confidence: 68%
“…In developed countries, it is a rarer cause of late-onset sepsis (LOS) among neonates compared to low- and middle-income countries. Candida prevalence in LOS varies from 1.9% in European countries [20,21] to 5.1% in United States [22 ▪ ] and can be as high as 6.3% in Argentina [26]and 11% in Brazil, with high mortality [25,27 ▪ ,28 ▪ ] (Table 2). It is believed that the higher incidence of Candida spp.…”
Section: Candida Spp Infectionsmentioning
confidence: 99%